The Effect of Physical Work Environment and Compensation on Employee Job Satisfaction - Andika Saputra; Anava Salsa Nur Savitri; Ahmad Ulil Albab Al Umar; Ahmad Jibril (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the influence of the physical work environment and compensation on employee job satisfaction. This research is quantitative research with a descriptive approach. The sample in this research was 32 permanent employees at PT Bank Rakyat Indonesia (Persero) Tbk Bandar Lampung Branch. The data collection technique was carried out by distributing questionnaires. The data analysis technique used is multiple linear regression analysis using Statictical Product Servive Solution (SPSS). The results of this research indicate that: 1) Physical work environment variables partially do not have a significant influence on employee job satisfaction at Bank Rakyat Indonesia (Persero) Tbk Bandar Lampung Branch, 2) Compensation variables have a positive and significant influence on employee job satisfaction at the Bank Rakyat Indonesia (Persero) Tbk Bandar Lampung Branch, 3) physical work environment variables and compensation simultaneously have a positive and significant influence on employee job satisfaction at Bank Rakyat Indonesia (Persero) Tbk Bandar Lampung Branch.